A novel technique of fabrication of nanoparticle acrylate doped polymer dispersed liquid crystal (PDLC) film. Issue 10 (1st August 2022) - Ahmad, Farzana; Jeon, A-Ri; Jeon, Young Jae; Jamil, Muhammad
Abstract: In order to investigate the electro-optical characteristics of the current polymer dispersed liquid crystal (PDLC) film, zinc acrylate nanoparticles (NPs ) were doped into the PDLC prepared samples. Generally for the fabrication of NPs –based PDLC film, two conventional methods such as the sandwich method and capillary methods are considered. In the conventional fabrication method of Np -doped PDLCs, the homogenous distribution of nanoparticles remained an unresolved issue. Particularly, upon the fabrication of Np -doped PDLC films, it is important to emphasis that nanoparticles are uniformly distributed inside the indium tin oxide (ITO) coated glass. For the purpose, here in this work, a new PDLC manufacturing method has been proposed to improve such shortcoming. Unlike the conventional method, the NPs acrylate layer was first coated on the ITO glass, which maintained evenly distributed NPs and then was placed onto the polymer/LC crystal mixture. By adopting the current PDLC fabricated method (with 1.0 wt% ZnA layer coating into PDLC film) the transmittance remained 93.9% and a good contrast ratio (CR) ∼ 7.0 was observed at a low driving voltage (∼ 20 V). Moreover the morphology study of current PDLCs showed a uniform size distribution of droplet morphology as well as a homogeneous distribution of NPs . Thus our investigations indicated that PDLC films prepared by this new technique achieved the goal of uniform distribution of NPs particles, homogeneous distribution of droplet morphology with the improved electro-optical characteristics. GRAPHICAL ABSTRACT: UF0001